Keefektifan Penggunaan Alat Flatjack Dibandingkan Dengan Tegangan Gravitasi Untuk Menghitung Tegangan Batuan Pada Lubang Bukaan Tambang Bawah Tanah CV. Tahiti Coal, Sawahlunto - Rahmad Setiawan; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Geomechanics testing is very important in mining industry, both open pit and underground mining. Geomechanics testing is aimed to determine the stress and the strength of the rocks. One example of insitu testing and destructive testing is the Flatjack testing method. The Flatjack tool is a tool developed by the FT UNP mining laboratory in September 2017. This tool is a development of the previous tool. The development Flatjack test results have never been tested and their effectiveness is unknown yet. The Flatjack tool needs to be tested by conducting a trial test at locations that are relevant to the function of the tool in order to obtain effectiveness.Based on the results of testing and direct observation in the field, the results of Flatjack tool test on branch 1 (10.5 kg / cm2), branch 2 (12.5 kg / cm2), and branch 3 (14 kg / cm2) were obtained. Based on the results of direct data collection in the field, the results of the calculation of gravitational forces on branch 1 (7.1285 kg / cm2), branch 2 (10.9859 kg / cm2), and branch 3 (14.583 kg / cm2) were obtained. Based on the results it can be concluded that the Flatjack tool needs to be calibrated so that the results obtained from the Flatjack tool test are more effective.Keywords: Hole opening, rock stress, Flatjack tool test, calculation of gravitational force, effectiveness